2012
DOI: 10.1158/1078-0432.ccr-12-1064
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment EBV-DNA Copy Number Is Predictive of Response and Toxicities to SMILE Chemotherapy for Extranodal NK/T-cell Lymphoma, Nasal Type

Abstract: Purpose: Extranodal NK/T-cell lymphoma, nasal type (ENKL) is an Epstein-Barr virus (EBV)-associated lymphoma for which a new chemotherapeutic regimen called SMILE (steroid, methotrexate, ifosfamide, L-asparaginase, and etoposide) recently showed promising results.Experimental Design: The amount of EBV-DNA was prospectively measured in whole-blood and plasma samples by real-time quantitative PCR from 26 patients registered in the SMILE phase II study.Results: Before treatment, the EBV-DNA was detected in 22 sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 30 publications
(39 reference statements)
7
54
1
Order By: Relevance
“…Several studies have shown that plasma EBV-DNA level is a sensitive surrogate biomarker for ENKTL tumor load. Persistently undetectable plasma EBV-DNA in ENKTL patients following treatment is correlated with superior survival [19,20]. In this study, patients who achieved undetectable plasma EBV-DNA following treatment with the Peg-GemOD regimen were still alive and maintained CR status, which indicates that plasma EBV-DNA level is an independent predictor for OS and PFS in advanced-stage ENKTL.…”
Section: Treatment-related Toxicitymentioning
confidence: 59%
“…Several studies have shown that plasma EBV-DNA level is a sensitive surrogate biomarker for ENKTL tumor load. Persistently undetectable plasma EBV-DNA in ENKTL patients following treatment is correlated with superior survival [19,20]. In this study, patients who achieved undetectable plasma EBV-DNA following treatment with the Peg-GemOD regimen were still alive and maintained CR status, which indicates that plasma EBV-DNA level is an independent predictor for OS and PFS in advanced-stage ENKTL.…”
Section: Treatment-related Toxicitymentioning
confidence: 59%
“…In contrast, Suzuki et al reported that pretreatment plasma EBV-DNA was detectable in only 43.8% (14 of 32) of patients, 35 which was lower than both ours and other previous studies. [31][32][33] Interestingly, in a recent study, 42 EBV-DNA was detected in whole blood in 22 of 26 (84.6%) patients who received SMILE (steroid, methotrexate, ifosfamide, L-asparaginase, and etoposide) chemotherapy. The different percentages of detectable pretreatment EBV-DNA in previous studies are probably the result of small sample sizes, sample collection differences, and different experimental assay, in addition to other unknown factors.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] In the phase II study from the NK-Cell Tumor Study Group, the overall response rate (ORR) was significantly higher in patients with …”
Section: Workupmentioning
confidence: 99%